When does science persuade (or not persuade) in high‐conflict policy contexts?. (19th March 2020) - Heikkila, Tanya; Weible, Christopher M.; Gerlak, Andrea K.
Abstract: Researchers struggle to understand the relationship between science and policy positions, especially the complicated interplay among the various factors that might affect the acceptance or rejection of scientific information. This article presents a typology that simplifies and guides research linking scientific information to policy positions. We use the typology to examine how characteristics of both scientific information and policy actors' existing policy positions affect the likelihood of changing, maintaining or reinforcing those policy positions. We analyse data from surveys conducted in 2015 and 2017 of policy actors engaged in contested policy debates over shale oil and gas development in Colorado, US. Our findings confirm expectations that policy actors will most likely maintain and reinforce their policy positions in response to scientific information. Our data also show that changes in policy positions depend on policy actors' risk perceptions, perceived issue contentiousness, networks and experience with science.